The Effect of Egyptian Consumer Values and Lifestyles on Organic Food Purchase Intention Applied on Z-generation - Farrag, Mayar (The Arab Journal of Administration, 2022)
This Study investigates which determinants of values and lifestyles affects the organic purchase intension of Egyptian consumers especially below 25 years old (generation Z) and compare the result of this age category with the sample including people who are above 25 years old. Thus, this paper adds a scientific value to previous studies. Data of the questionnaire were collected in 2020 from a random sample of 186 individuals from the city of Cairo (Egypt). Findings - Empirical results (using factor analysis and regression models) showed that lifestyle and values have a significant impact on organic food purchase intension. As for demographic variables, age had a significant effect on some factors of values and lifestyle of the Egyptian consumers. Moreover, age had a significant effect on organic food purchase intention. Concerning Z Generation consumer, the result indicated that Z generation age had no impact on values, while it had a significant effect on “healthy food eaters” (factor of Z generation consumer lifestyle). Originality/value-Attempt to test the VALS scale on the green consumers with a deep understanding of their demographics as well as defining organic food consumer profiles. Implications Results confirm importance of educating consumers about healthy lifestyle facilitate organic food purchase intention.